FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN DOMPET DIGITAL DALAM TINJAUAN EKONOMI ISLAM (STUDI PADA MASYARAKAT KOTA BANDA ACEH) - Murni, Seri; Khairi, Khairi; Fitri, Cut Dian (Jihbiz: Global Journal of Islamic Banking and Finance, 2024)
Currently, the use and use of digital wallets is widespread in almost all circles, including the people of Banda Aceh City. The use and utilization of this digital wallet cannot be separated from the factors of security, convenience and sharia compliance. This research aims to determine the influence of security, convenience and sharia compliance factors on the interest of the people of Banda Aceh City in using digital wallets. This research uses quantitative research where samples are taken using a cluster sampling technique from 99 people in the city of Banda Aceh. The data analysis method uses multiple linear regression analysis assisted by SPSS version 24. From the research findings, it can be concluded that (1) the security variable influences people's interest in using digital wallets, (2) the convenience variable influences people's interest in using wallets. digital, (3) the variable of sharia compliance influences people's interest in using digital wallets, and (4) simultaneously the variables of security, convenience and sharia compliance influence people's interest in using digital wallets